Efektivitas Memberdayakan Ekonomi Pada Program Komunitas Usaha Mikro Muamalat Berbasis Masjid di Masjid Miftahul Jannah Surabaya - Ardiansyah, Hanif; Nafik HR, Muhammad (Jurnal Ekonomi Syariah Teori dan Terapan, 2014)
The porpose of this research is to find out the effectiveness of Mosque-basedMicrobusiness Community Program to empowering mustahiqâs economy at Miftahul JannahÂ Mosque Surabaya.The research method of this research is a qualitative approach, case studies strategy,Â and descriptive analysis techniques which collecting data through interview, andÂ observation. The informants are members of Mosque-based Microbusiness CommunityÂ Program at Miftahul Jannah Mosque Surabaya, consist of seven people who had attandedÂ the program and has recieved assistance zakat productive in the form venture capital fromÂ Baitul Maal Muamalat through Mosque-based Microbusiness Community Program (KUM3).Based on the results of the research is Mosque-based Microbusiness CommunityÂ Program effective to empower mustahiqâs economy use productive zakat consist of ventureÂ capital, the mosque has a maximum role to facilitate the distribution of productive zakatÂ from Baitul Maal Muamalat to mustahiq evidenced by increasing three indicators, namelyÂ ruhiyah, partisipation, and business.